Effectiveness of Implementation of Regional Autonomy in the Border Area of Belu District - Sae, Donatus; Bere, Joseph Franky Leto; Bere, Agustinus (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research is a qualitative study. Data were obtained through field observations, literature studies, and interviews. Regional autonomy is a golden bridge for accelerating development in Indonesia, especially in peripheral areas. This development includes various aspects in accordance with the spirit of the Unitary State of the Republic of Indonesia. Belu Regency, as one of the border areas, has experienced positive changes in the implementation of regional autonomy, especially in the fields of tourism and cultural infrastructure.